Fusion of smart, multimedia and computer gaming technologies research, systems and perspectives - Sharma, Dharmendra; Favorskaya, Margarita; Jain, L. C.; Howlett, Robert J. 1954- (Springer International Publishing, 2015)
This monograph book is focused on the recent advances in smart, multimedia and computer gaming technologies. The Contributions include: · Smart Gamification and Smart Serious Games. · Fusion of secure IPsec-based Virtual Private Network, mobile computing and rich multimedia technology. · Teaching and Promoting Smart Internet of Things Solutions Using the Serious-game Approach. · Evaluation of Student Knowledge using an e-Learning Framework. · The iTEC Eduteka. · 3D Virtual Worlds as a Fusion of Immersing, Visualizing, Recording, and Replaying Technologies. · Fusion of multimedia and mobile technology in audioguides for Museums and Exhibitions: from Bluetooth Push to Web Pull. The book is directed to researchers, students and software developers working in the areas of education and information technol